Experience with Airway Management and Sequencing of Repair of Panfacial Fractures: A Single Tertiary Healthcare Appraisal in Najran, Kingdom of Saudi Arabia - A Retrospective Study - Daniels, John Spencer (Ann Maxillofac Surg, 2020)
INTRODUCTION: Special cooperation is required among surgeons and anesthetists in airway management during repair of panfacial fractures, due to problems of shared airway and occlusion. Several methods have been proposed for airway management and sequencing of repair of panfacial fractures. The main objective of the current study was to share our experience in the airway management and sequencing of repair of panfacial fractures. METHODS: This was a retrospective study of panfacial fractures in the Kingdom of Saudi Arabia from January 2008 to December 2018. Data collected included demographics, type of airway management, sequence of repair (as primary variables), and outcome of surgery (secondary variable), while surgeon and anesthetic expertise are confounders. Data were analyzed using IBM SPSS Statistics for Windows Version 25 (Armonk, NY, USA: IBM Corp). Results were presented as simple frequencies and descriptive statistics. Pearson Chi-square was used to compare categorical variables such as airway management and sequencing of repair with the panfacial fractures. Statistical significance was set at P ≤ 0.05. RESULTS: Overall, 1057 patients sustained different categories of maxillofacial bone fractures with 23 females and 1034 males (M:F of 46:1). A total of 43 male patients out of 1057 patients had panfacial fractures during the study period, giving a prevalence rate of 4.1%. Only the 43 male patients with panfacial fractures were analyzed. All cases were as a result of motor vehicular accident. Six (13.9%) patients had tracheostomy while 37 (86.1%) patients had submental intubation. “Bottom-up” and “outside-in” approach was used in 33 (76.7%) patients, while “top-bottom” and “inside-out” approach was used in 10 (23.3%) patients. DISCUSSION: Submental intubation was the major airway management of panfacial fracture, and “bottom-up” and “outside-in” approach was the main sequence of repair in our series. These approaches have been mentioned in the literature. CONCLUSION: From our study, victims of pan-facial fractures were found to be exclusively male with MVA as the sole etiological factor. Barring severe head injuries, which may necessitate the use of tracheostomy to sustain breathing over a longer period, submental intubation is extremely reliable as a mode of airway management during surgical treatment of panfacial fractures. The sequencing of repair of panfacial fractures can only be determined according to the case presentation rather than a predetermined one.